ANALISIS KOMPARATIF PERHITUNGAN PPH 21 SEBELUM DAN SESUDAH TARIF EFEKTIF RATA-RATA - Ningsih, Jiah Kurnia; Widayati, Neneng; Fauzi, Fauzi (E-Jurnal Akuntansi TSM, 2025)
The complexity in calculating Article 21 Income Tax (PPh 21) using the progressive tariff system has raised concerns regarding accuracy, fairness, and efficiency in tax administration, particularly within local government institutions. In response, the Indonesian government introduced the Average Effective Rate (TER) as a simplified alternative to improve tax withholding mechanisms. This study aims to compare the PPh 21 calculation before and after the implementation of TER in the Regional Financial Management Agency of Tangerang City. Using a quantitative approach, the study employs a one-sample t-test to analyse data from 83 employees. The results reveal a statistically significant difference between the PPh 21 amounts before and after TER implementation. The findings indicate that the TER policy contributes to a more streamlined, consistent, and equitable tax withholding process, reducing the risk of miscalculation and administrative burden. This study provides empirical evidence that supports the adoption of TER as an effective fiscal policy tool to enhance the efficiency of income tax management at the local government level. Future studies are encouraged to expand the sample and explore the long-term impact of TER on tax compliance and administrative performance across various public institutions.